Are the odds shifting against pharma in the fight for cheaper treatment for macular degeneration?. (31st October 2017) - Cohen, Deborah
Abstract : Doctors plan to prescribe bevacizumab despite legal threats from drug companies, and against GMC and NICE guidance. Responses to the policy and new legal rulings hint at a turning point in a long-running battle in which £0.5bn potential NHS savings are at stake, reports Deborah Cohen